Produção de argamassa de revestimento com a substituição parcial do agregado natural por resíduo de polipropileno - GARCIA, Adson de Sousa (2023)
The generation of polymeric waste has presented a broad environmental debate, due to the long decomposition time of these materials. Among them, Polypropylene (PP) waste stands out. The material, developed to facilitate an increasingly growing and dynamic consumer market, has brought with it an increase in the volume of polluting residues, especially in the pandemic scenario of COVID-19. In line with this problem, the consumption of mineral resources by civil construction is also responsible for major environmental impacts. In this sense, we sought to evaluate the technical feasibility of mortars for coating produced with crushed polypropylene waste. In order to meet the proposal of this research, the methodology was first based on the characterization of the aggregates constituting the mortar (granulometry, unit mass, water absorption and density). Subsequently, a rich mixture was defined for rendering 1;2.5 with a w/c factor of 0.6 with partial substitution of natural aggregate by artificial aggregate in the proportions of 0%, 2%, 4% and 6% by mass. After defining the mix, the fresh state tests were performed (consistency, incorporated air content, bulk density, and water retention). Then, the samples were molded and subjected to axial compression tests, flexural traction, bulk density, traction by diametrical compression, traction adhesion, modulus of elasticity, absorption by capillarity, absorption by immersion, and void index. Given the results, the mixture RPT-6 stood out, having presented the best behavior in relation to mass density, with an increase of 21%. Moreover, for the same mix, an improvement in mortar ductility was observed, with a reduction in elasticity modulus of approximately 49%. Regarding adherence, the coatings containing polypropylene residue remained within the range of 0.50 MPa, as well as the reference mixture. Thus, it is observed that the use of polymeric waste has technical feasibility for application as an aggregate in coating mortars. This is because, even though the results show reductions in mechanical strength, the lining mortars do not have a structural function and, therefore, no impediments were found regarding its use. Furthermore, it was found that the addition of this waste did not result in a loss of workability of the mortars evaluated.